Enrichment Strategies in Pediatric Drug Development: An Analysis of Trials Submitted to the US Food and Drug Administration. Issue 5 (13th February 2018) - Green, Dionna J.; Liu, Xiaomei I.; Hua, Tianyi; Burnham, Janelle M.; Schuck, Robert; Pacanowski, Michael; Yao, Lynne; McCune, Susan K.; Burckart, Gilbert J.; Zineh, Issam
Abstract : Clinical trial enrichment involves prospectively incorporating trial design elements that increase the probability of detecting a treatment effect. The use of enrichment strategies in pediatric drug development has not been systematically assessed. We analyzed the use of enrichment strategies in pediatric trials submitted to the US Food and Drug Administration from 2012–2016. In all, 112 efficacy studies associated with 76 drug development programs were assessed and their overall success rates were 78% and 75%, respectively. Eighty‐eight trials (76.8%) employed at least one enrichment strategy; of these, 66.3% employed multiple enrichment strategies. The highest trial success rates were achieved when all three enrichment strategies (practical, predictive, and prognostic) were used together within a single trial (87.5%), while the lowest success rate was observed when no enrichment strategy was used (65.4%). The use of enrichment strategies in pediatric trials was found to be associated with trial and program success in our analysis.